Seasonal variations in VO2max, O2-cost, O2-deficit, and performance in elite cross-country - Losnegard, T.; Myklebust, H.; Spencer, M.; Hallén, J. (The Journal of Strength and Conditioning Research, 2013)
Long-term effects of training are important information for athletes, coaches, and scientists when associating changes in physiological indices with changes in performance. Therefore, this study monitored changes in aerobic and anaerobic capacities and performance in a group of elite cross-country skiers during a full sport season. Thirteen men (age, 23 ± 2 years; height, 182 ± 6 cm; body mass, 76 ± 8 kg; V2 roller ski skating VO2max, 79.3 ± 4.4 ml/kg/min or 6.0 ± 0.5 L/min) were tested during the early, middle, and late preparation phase: June (T1), August (T2), and October (T3); during the competition phase: January/February (T4); and after early precompetition phase: June (T5). O2-cost during submaximal efforts, VO2peak, accumulated oxygen deficit (EO2-deficit), and performance during a 1,000-m test were determined in the V2 ski skating technique on a roller ski treadmill. Subjects performed their training on an individual basis, and detailed training logs were categorized into different intensity zones and exercise modes. Total training volume was highest during the summer months (early preseason) and decreased toward and through the winter season, whereas the volume of high-intensity training increased (all p < 0.05). There was a significant main effect among testing sessions for 1,000 m time, O2-cost, and EO2-deficit (Cohen`s d effect size; ES = 0.63-1.37, moderate to large, all p < 0.05). In general, the changes occurred between T1 and T3 with minor changes in the competitive season (T3 to T4). No significant changes were found in VO2peak across the year (ES = 0.17, trivial). In conclusion, the training performed by elite cross-country skiers induced no significant changes in VO2peak but improved performance, O2-cost, and O2-deficit.